Christoph Friedrich Reinhold Lisiewsky (1725 - 1794): [Katalog zur Ausstellung "Teure Köpfe. Lisiewsky - Hofmaler in Anhalt und Mecklenburg", Kulturstiftung Dessau Wörlitz, 29. August bis 31. Oktober 2010, Staatliches Museum Schwerin, 10. Dezember 2010 bis 6. März 2011] - Börsch-Supan, Helmut (Kataloge und Schriften der Kulturstiftung Dessau-Wörlitz, 2010)
Summary: The 18th century painter Christoph Reinhold Friedrich Lisiewsky attained the realistic effect of physical presence in his portraits through a painting method that required many sessions. This richly illustrated catalogue is the first monograph on the painter. Exhibition: Schloss Mosigkau (29.08 - 31.10.2010) and Staatliches Museum, Schwerin ( 10.12.2010 - 6.03.2011)